EKSPLORASI TRAUMATIS DAN REKONSILIASI TRAUMA DALAM BUKU KUMPULAN CERPEN B KARYA SASTI GOTAMA - Rani Nuzulul Laili; Rulia Hakiki Zavista; Brillian Septi Ega Ratna D; Ahmad Junaidi (Hiski Malang, 2025)
This research discusses the exploration of trauma themes and trauma reconciliation efforts in the short story collection B by Sasti Gotama published in 2022. This short story collection consists of 21 short stories that describe the dark side of the human soul, with an emphasis on psychic experiences, inner wounds, and existential conflicts experienced by the characters. This research uses a descriptive qualitative approach with literature study techniques, with analysis conducted based on the theory of trauma proposed by Cathy Caruth and the concept of trauma reconciliation by Dominick LaCapra, especially regarding the mechanisms of acting out and working through in the trauma healing process. The results show that each character in the short story experiences various forms of trauma with different responses, both implicitly and explicitly, and displays various reconciliation mechanisms. Some characters are trapped in the trauma cycle (acting out), while others try to heal their psychic wounds through the process of working through. 13 short stories perform a form of trauma reconciliation acting out; 7 short stories perform a form of trauma reconciliation working through; and 1 short story does both.